De la ruche-tronc à la ruche à cadres : ethnoécologie historique de l’apiculture en Cévennes - Ameline Lehébel-Péron; Daniel Travier; Alain Renaux; Edmond Dounias; Bertrand Schatz (Revue d'ethnoécologie)
On the grounds that beekeeping of the single domesticated honeybee looks at first sight homogenous throughout whole Europe, understanding the evolution of this activity at the very local level is generally overlooked. Such understanding is nonetheless crucial to conceive appropriate community-based resource management in socioecological systems that have been profoundly imprinted by beekeeping activities. We carried out an ethnoecological history study focusing on local knowledge regarding beekeeping in the Cevennes National Park (southern France). By combining the analysis of archival documents, scientific literature and personal testimonies from elderly Cevennes dwellers, this dive into history has allowed us to reconstitute the major episodes of beekeeping in Cevennes, by considering the modifications of chosen beehive models and bee landraces, as well as the valorization of beehive products following the evolving social and economic circumstances. Most salient features, such as the first evidence of the use of log hives in the early 17th century, were thus time-stamped and retrospectively set into context. Artisanal beekeeping of the local black bee hosted in log hives has persisted until the 1970s date of the transition to modern beekeeping using frame hives, selected bee landraces, and a professionalization of the local honey trade sector. Beekeepers from the Cevennes region only lately stepped from a domestic and landscaped beekeeping, which was optimized in a context of self-sufficient pluriactivity, into an intensive beekeeping driven by the search for maximized honey yields and supported by a diversification and a hybridization of bee landraces. Such combined historical and biocultural perspectives of beekeeping in Cevennes should serve to elaborate reasonable goals for conservation and should help conciliating the preservation of a patrimonial and traditional beekeeping along with the enhancement of a yet emerging local honeybee market.